Prediction of cardiorrespiratory fitness by screen time in schoolchildrens - Amanda de Oliveira; Flávio Ricardo Guilherme; Stevan Ricardo dos Santos; Maria Teresa Martins Fávero; Vânia Renata Guilherme; Wilson Rinaldi (Revista da Educação Física)
The time spent in front of the screens, results in accumulations of sedentary behavior, which is related to health damages to adolescents, such as a low cardiorespiratory fitness. In this sense, this study aimed to predict cardiorespiratory fitness through screen time in schoolchildren. Cross-sectional study, as a sample composed of 2.764, of which 1.370 boys and 1.394 girls between 10 and 18 years old were the public school system of Paranavaí, Paraná, Brazil The self-report questionnaire was used to estimate screen time (ST) and cardiorespiratory fitness (CF) was estimated using the 20-meter multi-stage test, and to verify the predictive power of the screen time in relation to CF, the Roc curve was used. The results showed that screen time was considered a good predictor of cardiorespiratory fitness in boys (weekdays, weekends and all week), and in general (boys and girls) only for weekdays (Monday to Friday). In the survey, the screen time cut-off for boys on weekdays was 137 minutes  (CI: 65-43), at weekends of 165 minutes (58-51) and general of 156 minutes (64-45). For the general sample (girls and boys), the cut bridge on weekdays was 142 minytes (64-44). For the girls the screen time had no predictive power (CI> 0.50) and consequently the cut-off point was not verified. Thus, it can be concluded that the screen time in boys and in general (only weekdays) was able to predict cardiorespiratory fitness and that this variable of easy application can be an important tool to predict CF in the school environment.